PENGARUH PERLAKUAN SKARIFIKASI TERHADAP DAYA KECAMBAH TANAMAN SAGA POHON (Adenanthera pavonina L.) - Cindy Yurike Aprilia, Liman, Muhtarudin dan Agung Kusuma Wijaya (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This research aimed to investigate the effect of various scarification treatments on the germination of tree saga seeds (Adenanthera pavonina L.). This study used a completely randomized design (CRD) with 6 treatments and 3 replications. The treatments in this study were P0 (control), P1 (soaked using distilled water for 24 hours), P2 (soaked using hot water 60 °C for 15 minutes), P3 (sanded skin), P4 (soaked using 1% H2SO4 for 30 minutes), and P5 (soaked using goat urine for 30 minutes). The data obtained were analyzed by Analysis of Variance and continued with the Least Significant Difference Test (LSD) level of 5%. The results showed that the treatment had a very significant effect (P <0.01) on germination rate. The best treatment that can increase the germination of a tree saga seeds (Adenanthera pavonina L.) was by eroding the seed skin using sandpaper. This treatment can produce an average germination of 78.89%, while the treatment that produce the highest abnormal seeds was found in the treatment by soaking using 1% H2SO4 for 30 minutes. The treatment that produce normal seeds, dead seeds, and the highest fungus-stricken seeds were found in the treatment by eroding the seed skin using sandpaper. The treatment that produced the highest hard seed was control. Keywords: Germination, Saga, Scarification.